The stochastic demography of two coexisting male morphs. - Smallegange, I; Coulson, T (2011)
Abstract. If genetically distinct morphs coexist under a range of natural conditions, they should have equal long-run fitnesses across a wide range of different stochastic environments. In other words, the sequence and frequency of good and bad environments should not substantially impact long-run growth rates. When different morphs have contrasting life histories that vary with environmental conditions, however, it seems improbable that growth rates can be equivalent across a range of stochastic environments without invoking a strong stabilizing mechanism to explain their persistence. As yet, there has been no research characterizing the long-run stochastic growth rate (lambdaS) of different morphs across a wide range of stochastic environments. Assuming density independence, we show that the two genetic male morphs in the bulb mite (Rhizoglyphus robini-fighters, which are able to kill other mites, and benign scramblers-have similar lambdas in different Markovian environments (different simulated random sequences of good and bad habitats). Elasticity analyses revealed that Xs was most sensitive to perturbation of adult survival rate. A slight (biologically and statistically realistic) increase in scrambler adult survival equalized scrambler and fighter X,. The fitness equivalence of the two morphs suggests that stabilizing mechanisms, such as density or frequency dependence, required to maintain their coexistence, are weak. We advocate that stochastic demography can offer a powerful approach to identify and understand the circumstances under which genetic polymorphisms can be maintained in stochastic environments.